2017
DOI: 10.1590/0101-60830000000136
|View full text |Cite
|
Sign up to set email alerts
|

Music performance anxiety: a critical review of etiological aspects, perceived causes, coping strategies and treatment

Abstract: Background: Music performance anxiety (MPA) is understood as a sub-type of social anxiety and is characterised by fears of a musical presentation. Objective: To carry out a critical literature review on clinical and etiological aspects, perceived causes, coping strategies and treatment of MPA. Methods: Electronic databases PubMed, PsycINFO and Lilacs as well as specific periodicals were used based on the keywords symptoms, diagnosis, aetiology, perceived causes, coping strategies and treatment. Results: MPA is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 50 publications
1
70
0
1
Order By: Relevance
“…Factors like age, gender, the kind of musical instrument, musical background, musical perception, perfectionism, and emotions compose the group of personal variables that can interfere more or less on the MPA levels [4,7].…”
Section: Mpa Pathogenesis Susceptibility and Vulnerabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Factors like age, gender, the kind of musical instrument, musical background, musical perception, perfectionism, and emotions compose the group of personal variables that can interfere more or less on the MPA levels [4,7].…”
Section: Mpa Pathogenesis Susceptibility and Vulnerabilitymentioning
confidence: 99%
“…In the musical environment, MPA has been called as "stage fright" although MPA encompasses something much bigger than that [4]. The reason is that MPA has three axes that complement each other in terms of subjective manifestations of this picture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saying that ‘I get nervous or anxious’ or ‘I need to work on my nerves’ is acceptable and approached with a constructive attitude. PA has been documented in a number of settings, but particularly in the music profession, being termed music performance anxiety (MPA) …”
Section: Lessons Learned From Musicmentioning
confidence: 99%
“…Performance anxiety (PA) extends beyond the normal, routine, daily anxieties and stresses, to a potentially debilitating anxiety in the context of a ‘performance’. It is more a fear of being negatively judged than a fear of underperforming, although this fear may contribute. A number of MPA management strategies have been reported to be beneficial, including cognitive behavioural therapy and the use of medications, such as beta‐blockers; However, further studies to establish treatment efficacy is required, as only modest responses may be observed .…”
Section: Lessons Learned From Musicmentioning
confidence: 99%